61 LEFT ATRIAL RESERVOIR AND STIFFNESS IN PATIENTS WITH WILD-TYPE TRANSTHYRETIN AMYLOID VS HYPERTROPHIC CARDIOMYOPATHY. (15th December 2022) - Campisi, Mariapaola; Trimarchi, Giancarlo; De Sarro, Rosalba; Poleggi, Cristina; Luongo, Alfredo; Teresi, Lucio; Lofrumento, Francesca; Restelli, Davide; Recupero, Antonino; Zito, Concetta; Di Bella, Gianluca; De Gregorio, Cesare
Abstract: Objectives: Left atrial (LA) function can be investigated by advanced ultrasound speckle tracking modality, much better than in the past. Modern ultrasound technology allows attaining myocardial deformation profiles from both ventricular and atrial chambers. Each of the 3 components of LA function [reservoir, also known as peak longitudinal strain (PALS); conduit and pump] can be impaired in various chronic diseases. We previously demonstrated that PALS (reservoir) and pump function weaken in patients with cardiac transthyretin amyloidosis (ATTR) and hypertrophic cardiomyopathy (HCM). In the present study we sought to recognize LA stiffness (LAst), a relatively novel marker of atrial dysfunction, in the same clinical settings. Methods: 17 patients, 9 with ATTR wild-type (wt) and 8 with non-obstructive HCM, mean aged 67±12 years, were investigated by using transthoracic color-Doppler and strain ultrasound equipment. LV mass index (LVMI), LA area index (LAAI), LV ejection fraction (LVEF), E/E' ratio, LV global longitudinal strain (GLS), PALS and LAst were assessed in both groups. LAst was calculated by PALS/E/E' ratio, as suggested by studies. Results: LVMI and LAAI were similar in the 2 groups: 171±40 vs 161±51 g/m 2.7 and 14±3 vs 16±4 cm/m 2.7 in ATTRwt vs HCM, respectively (p=NS). However, patients in the former group showed poorer LV diastolic and systolic function (LVEF was 47±9 vs 58±5%, respectively, p<0.01), as well as GLS (9.5±2.2 vs 12.6±2.8, respectively, p=0.02). PALS and LAst were more impaired in ATTRwt compared to HCM patients ( Figure ), despite similar LA chamber size. Considering that LAst value >0.65 has been reported as a predictor of adverse LA morphofunctional remodeling, both groups were considered at risk for atrial dysfunction, but mainly the former one. Conclusions: Although present findings were achieved by a small patient population, LA reservoir and stiffness were impaired in patients with ATTRwt more than in those with HCM. Left atrial dysfunction may not be strictly related with LVMI or LA size, but with LV-GLS, confirming an atrio-ventricular functional interplay in cardiac amyloidosis. Further larger study is needed to corroborate present results.